Water quality management strategies for super‐intensive culture of Penaeus vannamei with biofloc system: A case study in Virginia, USA - Pimentel, Otávio Augusto Lacerda Ferreira; de Oliveira Ramiro, Bianca; Carvalho, Andrezza; Höffling, Flávia Banderó; Miyai, Caio Akira [UNESP]; Wasielesky, Wilson; Schwarz, Michael H.; van Senten, Jonathan; Urick, Stephen; McAlhaney, Ethan; Gonçalves, Fernando H.; Krummenauer, Dariano (Wiley, 2025)
Abstract The aim of this case study was to investigate and describe water quality and growth performance of Penaeus vannamei produced in a super‐intensive biofloc system (BFT) under diverse water conditions (seawater and low‐salinity water) in the state of Virginia, USA. Three individual indoor super‐intensive grow‐out trials were conducted using a stocking density of 500 shrimp m −3 at salinities of 23 g L −1 for 70 days (TI), 28 g L −1 for 69 days (TII), and 2 g L −1 for 30 days (TIII). Key water quality management strategies included: (TI) BFT system; (TII) BFT system and probiotic; (TIII) BFT system, probiotic, water reuse, and artificial substrate. TII exhibited the highest mean total ammonia nitrogen (TAN) concentration (2.60 mg L −1 ), and the greatest variation in TAN levels, which were controlled from day 35 onward. TAN levels remained relatively stable in TIII. TI exhibited the highest mean nitrite concentration (3.66 mg L −1 ) and the greatest variation, with a spike that was successfully controlled from day 35 onward. In contrast, nitrite concentrations in TII displayed a continuous upward trend from day 28 without any indication of stabilization. Nitrite concentrations in TIII remained consistently low, never exceeding 0.5 mg L −1 throughout the experiment. Nitrate concentrations exhibited a consistent upward trend across all trials. The final weight of shrimp in TI and TII was 11.03 g and 13.62 g respectively, while in TIII it was 4.86 g. Survival rates were 77.67% in TI, 86.00% in TII, and 87.00% in TIII. Yield values were 4.28, 5.81, and 2.12 kg m −3 for TI, TII, and TIII, respectively. Our findings indicated slower nitrification rates in TI and TII compared to TIII. Water reuse, probiotic inoculation, and artificial substrates in TIII resulted in significantly lower and more stable levels of ammonia and nitrite compared to TI and TII, indicating a mature system with improved control for nitrogenous compounds. These findings demonstrate the successful application of integrated BFT strategies, including water reuse, probiotic inoculation, and artificial substrates, in enhancing the super‐intensive indoor production of P. vannamei using both seawater and low‐salinity water. These results have significant implications for the development of shrimp farming in the state of Virginia, USA.